Socioculturally Focused Reclamation: Reimagining the Post-extraction Landscape of Giant Mine - Gamble, Haley (University of Waterloo, 2020)
Canada is a nation of extraction, a truism that predates its confederation and is as iconic as its fur trade. Though the modern reality of extraction differs widely from this historical archetype natural resources continue to be a critical part of the Canadian economy. Today the minerals industry is one of the biggest in Canada and accounts for about five percent of the country’s annual GDP.1 This economic stimulus is the product of thousands of mines and quarries operating across the country to deliver the mineral wealth of Canadian ground to the global market. This production process is lengthy, intensive and necessitates the disturbance and contamination of vast tracts of land to extract the substances deemed vital to modern society. Once extraction is complete mines leave behind an atrophied and often toxic landscape, creating an expensive and demanding liability in the form of reclamation, a responsibility that is easily neglected or eschewed by the owner. As a result, many mines are insufficiently remediated or abandoned all together making them orphans of the state that plague local communities with hazards and Canadian taxpayers with cleanup costs. These orphan mines are particularly common in the north where natural resource extraction is the backbone of the economy and the land is sparsely populated and developed. One of these sites is Giant Mine, a former gold mine that operated for over fifty years outside Yellowknife, Northwest Territories and is one of the most contaminated sites in Canada. The property is now the responsibility of the federal government and is slated for an interminable remediation project that only addresses immediate human health and safety risks. This is emblematic of most abandoned mines and numerous reclamation projects where biophysical restoration is frequently the sole priority. This technical focus is often problematic as it overlooks the specificity and complexity of context. In the case of Giant Mine this includes a complex sociocultural fabric of Indigenous-settler ...